PENGEJAWANTAHAN ASAS PERADILAN SEDERHANA, CEPAT DAN BIAYA RINGAN YURISDIKSI HUKUM PENGADILAN TINGGI AGAMA PEKANBARU - Marta, Fajar; Sutomo (UIR Law Review, 2025)
Abstract: The implementation of the principles of simple, swift, and low-cost justice in the current development of law is influenced by digitalization, therefore the Supreme Court of the Republic of Indonesia issued legal regulation PERMA Number 7 of 2022. In implementing the technical guidelines of PERMA 7 of 2022, the Supreme Court of the Republic of Indonesia issued Circular Letter No. 1 of 2023 concerning Procedures for Summons and Notifications via Registered Mail, which was then realized in a Cooperation Agreement on the Delivery of Registered Letters between the Supreme Court of the Republic of Indonesia and PT. Pos Indonesia (Persero) as a serious and focused commitment to realizing an electronic, modern, efficient, and fast court system. The purpose of this study is to determine how the principles of simple, fast, and low-cost justice are implemented in the jurisdiction of the Pekanbaru Religious High Court, and what are the obstacles to summons/notification by registered mail in the settlement of cases under the jurisdiction of the Pekanbaru Religious High Court. This research method is through digital literature study, while the data used in this research is primary data obtained directly from the source, namely the Letter of the Director General of the Religious Court Agency Number: 3867/DJA/TI1.1.1/XII/2024, the Performance of the Badilag Work Unit, and the Case Tracking Information System (SIPP). Keywords: Implementation, Low Cost, Registered Letter, Digitization.